Bank mergers in the financial crisis: A competition policy perspective - Michael Hellwig; Falk Hendrik Laser (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We analyze a large merger in the Dutch banking market during the financial crisis using disaggregated data. Based on a merger simulation model, we evaluate merger-induced changes in the interest rates for savings accounts. We find that the merging banks decreased interest rates by 3 to 5 percent and competitors by up to 1 percent. These anti-competitive effects translate into a loss of consumer welfare by roughly 69 million euros in 2010. We identify heterogeneous effects indicating that less educated consumers with lower savings are most affected. Our findings highlight the important role of competition policy during financial crisis mitigation.
Keywords: D22; G21; G34; L11; L25; L40; L41; 330; antitrust; competition policy; merger analysis; state aid; retail banking; random-coefficients logit models; differentiated products